Influence of zinc oxide nanoparticles (ZnO NPs) on the hemocyte count and hemocyte-mediated immune responses of the Greater Wax Moth Galleria mellonella (Lepidoptera: Pyralidae) - NURULLAHOĞLU, ZAHİDE ULYA (My University, 2022)
In this study, we examined the effects of different doses (100, 500, 1000, 3000, and 5000 ppm) of zinc oxide nanoparticles (ZnO NPs) on the total hemocyte count and hemocyte-mediated immune responses of the Greater Wax Moth Galleria mellonella (Lepidoptera: Pyralidae). The results showed that NPs caused a decrease in hemocyte count at 1000, 3000, and 5000 ppm doses. To investigate the effects of ZnO NPs on the encapsulation and melanization response of G. mellonella, the pre-dyed Sephadex chromatography beads were injected into the hemolymph of each last-instar larva. Larvae were dissected in the 4th and 24th hours after the injection. The level of the encapsulation response and melanization status around the beads were determined under microscopy. The analyses of the beads injected into the insects as encapsulation targets revealed that the number of weakly encapsulated beads increased significantly at 100, 1000, 3000, and 5000 ppm doses when compared to the control group after a short (4-h) post-injection. The number of melanized beads increased significantly at 100, 1000, and 3000 ppm doses in comparison to the control group after the short (4-h) post-injection. Finally, the number of melanized beads decreased significantly at 1000 and 5000 ppm doses when compared to the control group after the long-term (24-h) post-injection.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Kimya; Biyokimya; Alkoloidler; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Chemistry; Biochemistry; Alcaloides; Health Sciences; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); TOKSİKOLOJİ; CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); TOXICOLOGY; Toksikoloji; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Sağlık, Toksikoloji ve Mutajenez; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Pharmacy; Toxicology; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Health, Toxicology and Mutagenesis; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Galleria mellonella; encapsulation; melanization; hemocyte count; zinc oxide nanoparticle; INFECTION; TOXICITY; INSECT; CELLS; MODEL; NANOMATERIALS; MELANIZATION; NUMBER; LARVAE; Galleria mellonella; encapsulation; melanization; hemocyte count; zinc oxide nanoparticle